Thermal colloid programming - Raphael Fortulan; Noushin Raeisi Kheirabadi; Alessandro Chiolerio; Andrew Adamatzky (Scientific Reports)
Abstract This paper investigates the computational capabilities of colloidal systems, focusing on the integration of Boolean logic operations within gold nanoparticle suspensions under varying temperature conditions. As climate change, artificial intelligence, and privacy concerns present increasing challenges for massively parallel and low-power computing devices, there is a growing demand for novel computing substrates, and colloids offer a promising avenue for developing energy-efficient and locally deployable systems. Our research explores how temperature impacts the behavior of suspended nanoparticles and, consequently, their interactions and computational performance. Our findings demonstrate that colloidal systems can perform Boolean operations, which can be modulated through temperature changes. By showcasing the versatility of these systems, this study underscores the significance of exploring unconventional computing paradigms and lays the foundation for future research into liquid-based computational applications.